Antibiotic Resistance in Bangladesh: Should Take Necessary Action Before the Situation Goes Out of Control! - Rahman, AKM Shahidur (KYAMC Journal, 2022)
Abstract not available KYAMC Journal Vol. 13, No. 01, April 2022: 1-3